2018
DOI: 10.1093/dote/doy015
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of eosinophilic esophagitis: a systematic review of epidemiology and disease course

Abstract: SUMMARYEosinophilic esophagitis is a chronic immune-mediated esophageal disorder. For its timely diagnosis, clinicians must recognize common symptoms, and understand differences in symptoms across patient groups. The aim of this study is to systematically review the epidemiology and natural history of eosinophilic esophagitis. The MEDLINE, Embase, and Cochrane databases were searched from 1974 to February 2017 for studies describing the epidemiology and natural history of eosinophilic esophagitis. Congress abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
118
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(136 citation statements)
references
References 48 publications
5
118
0
13
Order By: Relevance
“…The time at which each study was developed, differences in the threshold of eosinophil count defining EoE and in how patients with a response to proton pump inhibitors (PPIs) were considered, as well as regional variations, are the most relevant explanations for the broad range of incidence and prevalence provided by this systematic review. The recent consideration that patients who respond to PPIs are within the spectrum of the disease rather than considered a different entity, along with new data available from 2018 that provides the highest frequency for the disease reported so far (and not included in recent reviews), makes the previously reported prevalence and incidence figures outdated.…”
Section: Introductionmentioning
confidence: 99%
“…The time at which each study was developed, differences in the threshold of eosinophil count defining EoE and in how patients with a response to proton pump inhibitors (PPIs) were considered, as well as regional variations, are the most relevant explanations for the broad range of incidence and prevalence provided by this systematic review. The recent consideration that patients who respond to PPIs are within the spectrum of the disease rather than considered a different entity, along with new data available from 2018 that provides the highest frequency for the disease reported so far (and not included in recent reviews), makes the previously reported prevalence and incidence figures outdated.…”
Section: Introductionmentioning
confidence: 99%
“…The predominant EoE clinical symptoms are dysphagia, feeding dysfunction, food impaction, abdominal pain and vomiting. Those symptoms may vary with age, sex and race of the patient . Clinical and epidemiological studies indicate EoE is an allergic disease, which develops due to multifactorial interplay of genetic, immunological and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, T H 2 cells are also responsible for IL‐13 and IL‐5 production, which induce the proliferation and survival of eosinophils, in the oesophageal epithelial layer, in response to food allergen intake . In that sense, the presence of 15 eosinophils, or more, per high power field (≥15 eos/HPF), in at least one biopsy sample, differentiates EoE from gastroesophageal reflux disease (GERD), as they present symptoms overlap . In association with the increased eosinophilia, clinical studies have shown mast cells to accumulate in oesophageal mucosa .…”
Section: Introductionmentioning
confidence: 99%
“…Studies in adults have reported that the peak incidence occurs between 30 and 50 years (8,9) . With regard to gender, the literature shows a higher prevalence in males (3) . Despite the higher prevalence of females in our study, we observed an equality (1:1) in the analysis of the group with positive biopsy, however with no statistical significance.…”
Section: Endoscopic and Histological Correlationmentioning
confidence: 99%
“…EoE is more common in males and can affect all age groups, with peak prevalence in adults between 30 and 50 years. The incidence (1 to 20 new cases per 100,000 inhabitants per year) and the prevalence (13 to 49 cases per 100,000 inhabitants per year) of the disease vary widely in North America and in Europe and has increased dramatically over the years (2,3) .…”
Section: Introductionmentioning
confidence: 99%